Performance, gut morphometry and enzymatic activity of broilers fed neonatal supplementation in housing - Tatiane Souza dos Santos; Adriano Barbieri; Robert Guaracy Aparecido Cardoso Araujo; Gustavo do Valle Polycarpo; Daniela Felipe Pinheiro; Valquíria Cação Cruz-Polycarpo (Acta Scientiarum. Animal Sciences, 2018)
The objective was to evaluate the performance, relative organ weight, morphometry, intestinal length and pancreatic enzyme activity of broilers receiving neonatal supplementation. A total of 900 Cobb 500 broiler chicks was housed in 30 boxes of 2.5 m². The treatments were divided in a completely randomized design with six replications, and consisted of five inclusion levels (0.0, 2.5, 5.0, 7.5 and 10 grams per bird). The supplement used was based of amino acids, vitamins and minerals, which was provided on the ration on the first day in the housing. Statistical analysis was performed using SAS (2008) and when significant broken down using a polynomial regression. Due to the inclusion of the neonatal supplement in the period from one to seven and one to 21 days of age, the feed intake presented a linear effect and the weight gain, a quadratic effect. The relative weights of the gizzard and liver showed a quadratic effect, and the inclusions of 4.18 and 3.41 grams/bird provided the lowest weights, respectively. The jejunum villi height decreased with supplementation as well as the activity of pancreatic lipase. It can be concluded that neonatal supplementation benefited the performance of birds up to 21 days of age.